Demographic Window of Opportunity in Nepal - Chalise, Hom Nath (Nepal Population Journal, 2018)
The demographic dividend (or window of opportunity) is the period during which a country's population experiences age structures that are highly favourable for development. Greater proportion of population becomes young and working age group. This cuts spending on dependents and spurring economic growth. Demographic dividend has importance in the national development if it is understood well and planned well for the national development. Nepal has already entered in demographic window of opportunity and this dividend phase ends around 2045. Government is lacking to utilize this dividend in the absence of stable government and proper policy requirements.